New Constitutionalism and the EU: Its Limits and Prospects beyond the COVID-19 Pandemic. Issue 4 (2nd October 2022) - Gill, Stephen; Biscahie, Thibault
Abstract: A key question for today is how far the apparent loosening of austerity following the COVID-19 pandemic in the form of the July 2020 European Recovery Plan of 750 billion euros, constitutes a first step towards debt mutualization (sharing of debts to fund recovery among EU Member States) but also whether it signals a move away from the neoliberal legal and political limits associated with neoliberal new constitutionalism measures, epitomized in the EU by the Maastricht Treaty and the Stability and Growth Pact. We think this prospect is unlikely – in the absence of significant political pressures demanding and creating alternative futures and promoting radical change. In lieu of paradigmatic change, Next Generation EU resembles a pragmatic shift – with indeed some innovative traits – triggered by two main motives: responding to the urgent pandemic shock, but most importantly tackling the lasting effects of economic and political imbalances, in an attempt to tame some of the socio-political tensions and risks of disintegration resulting from the mismanaged Eurozone crisis.